The effects of the interest rates on the government bond liquidity - Makkonen, Joonas Santeri (2024)
Understanding the impact of interest rates on the government bond market is crucial, given that interest rates have traditionally been the primary instrument of monetary policy for central banks. While extensive research has been conducted on the determinants of government bond liquidity, the influence of interest rates during the quantitative easing using Wu-Xia shadow rate remains relatively underexplored. Purpose of this thesis is to study the effects of interest rates on government bond liquidity. To conduct this study, 10-year benchmark government bonds from Finland, Italy and the US will be used. Interest rates will be studied by using Federal Funds Rate, the ECB key rate and Wu-Xia shadow rate to be able to capture the effects of the quantitative easing and the unusually low interest rates. Liquidity is examined by bid – ask spread and the data used are from September 2005 to December 2022. The timeline covers European debt crisis, Covid-19 outbreak, negative interest rates, and various inflation levels.